Role of myeloid-derived suppressor cells in the promotion and immunotherapy of colitis-associated cancer. Issue 2 (13th October 2020) - Wang, Yungang; Ding, Yanxia; Deng, Yijun; Zheng, Yu; Wang, Shengjun
Abstract : Colitis-associated cancer (CAC) is a specific type of colorectal cancer that develops from inflammatory bowel disease (IBD). Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that are essential for the pathological processes of inflammation and cancer. Accumulating evidence indicates that MDSCs play different but vital roles during IBD and CAC development and impede CAC immunotherapy. New insights into the regulatory network of MDSCs in the CAC pathogenesis are opening new avenues for developing strategies to enhance the effectiveness of CAC treatment. In this review, we explore the role of MDSCs in chronic inflammation, dysplasia and CAC and summarize the potential CAC therapeutic strategies based on MDSC blockade.